Removal of antibiotic sulfamethoxazole in water using rapid growing ZnO nanorod - Ahmadipour M.; Rezaei Ardani M.; chrouda A.; Pang A.L.; Mohd Razip Wee M.F.; Satgunam M. (Elsevier Ltd, 2025)
The primary objective of this research is to synthesize ZnO vertical nanorods on a conductive substrate through a novel approach. In this method, ZnO nanorods are grown on kanthal wires using the direct heating (DH) technique. The study investigated the application of ZnO nanorods in photodegradation, specifically in removing Sulfamethoxazole (SMX). Through comprehensive analysis techniques, including XRD, FESEM, and TEM, the successful growth of ZnO nanorods on kanthal wires is confirmed. Their photocatalytic activity in SMX degradation is evaluated at varying concentrations (3 ppm, 5 ppm, 10 ppm) under UV light. Notably, the ZnO sample produced under 80 W power and 120 min emerges as the most promising, exhibiting a high surface area of 36 m2g-1, larger length of 755 nm, and lower diameter of 12 nm, as well as superior SMX photodegradation percentages of 87.64 % (3 ppm), 77.86 % (5 ppm), and 51.84 % (10 ppm) after 60 min. These findings highlight the potential of synthesizing ZnO nanorods via DH technique as an efficient and sustainable solution for removing pharmaceutical contamination in water sources. ? 2024 Elsevier Ltd and Techna Group S.r.l.